An Assessment of the Socio-Economic Impact of Terrorism in Northern Nigeria: The case of Boko Haram Insurgency - MBELI, ARMSTRONG-LOUIS NDAPTSO (Graduate School of International Studies Ajou University, 2015)
The purpose of this study is to assess the Socio-economic impact of terrorism in Northern Nigeria with special focus on Boko Haram insurgency in that part of the region. I will begin by giving an insight into the meaning of terrorism, examining different definitions as variously put forward by different scholars. The study then settled on one working definition that formed basis upon which it was founded. This definition by David Rodin which says, Terrorism is the deliberate, negligent, or reckless use of force against noncombatants, by state or non state actors for ideological ends and in the absence of a substantively just legal process. Best resonated with the objectives of the study . My literature review will be done with a wealth of extractions from well-known authors and rich sources of publications to re-emphasize the fact that their ideologies were in line with the study objectives. The literature review will focused a lot on the research questions and objectives. Thus, the areas largely explored in the literature review will be the social impacts of terrorism, economic impacts, as well as impacts of acts of terror and terrorism on the prospects for regional integration in Nigeria. To further examine the implications of terrorism on northern Nigeria, and by extension the whole of Nigeria, the study will be divided into five chapters. In chapter one, will define the research study and puts it into context through the introduction and background of study. This chapter also presents the Research Questions, and hypothesis and the methodology. Chapter two look at the literature review puts the study in context by first examining international terrorism, highlighting the history of modern international terrorism and examining its relation to Terrorism and Religion. Furthermore, this chapter examines theoretical frame work. Chapter three will analyze terrorism in Northern Nigeria with main focus on Boko Haram. This chapter will present a history of terror in Nigeria and also examines terrorism in northern Nigeria and some specific acts of terror that have been experienced in northern Nigeria. The chapter also discusses Boko Haram as a terror group and their motives in northern Nigeria. Chapters four will be the most important chapter in this study because it will elaborate on the Socio-Economic impacts of Boko Haram insurgency in northern of Nigeria and the final chapter will round up with the Summary of Findings, Conclusions and Recommendations.
학위논문(석사)--Graduate School of International Studies Ajou University :국제개발협력과,2015. 8